Autoantibody clustering of lupus-associated pulmonary hypertension. Issue 1 (2nd December 2019) - Mizus, Marisa; Li, Jessica; Goldman, Daniel; Petri, Michelle A
Abstract : Objective: To define the SLE phenotype associated with pulmonary hypertension using multiple autoantibodies. Methods: 207 (8%) patients with SLE with pulmonary hypertension, defined as a right ventricular systolic pressure greater than 40 mm Hg on transthoracic echocardiogram or as pulmonary artery dilatation on CT of the chest, were identified from the Hopkins Lupus Cohort (94.2% female; 56.5% African–American, 39% Caucasian; mean age 45.6 years). 53 patients were excluded from the clustering analysis due to incomplete autoantibody profiles. Agglomerative hierarchical clustering algorithm with Ward's method was used to cluster the patients with pulmonary hypertension, based on their autoantibodies. Autoantibodies used in the clustering analysis included lupus anticoagulant, anticardiolipin, anti-beta 2 glycoprotein I, antidouble-stranded DNA, anti-Sm (anti-Smith), antiribonucleoprotein, false positive-rapid plasma reagin, anti-Ro, anti-La and hypocomplementaemia (C3 ever low or C4 ever low). The Dunn index was used to internally validate the clusters. Bootstrap resampling derived the mean Jaccard coefficient for each cluster. All analyses were performed in R V.3.6.1 using the packages cluster, fpc and gplots. Results: A significantly higher prevalence of pulmonary hypertension in African–American patients with SLE, compared with Caucasian patients with SLE (11.5% vs 5.9%, p<0.0001), was found. Based on equivalent Dunn indices, the 154 patients with SLE-associated pulmonary hypertension with complete autoantibody data were divided into five clusters, three of which had mean Jaccard coefficients greater than 0.6. Hypocomplementaemia, renal disorder and age at diagnosis significantly differed across clusters. One cluster was defined by antiphospholipid antibodies. One cluster was defined by anti-Ro and anti-La. One cluster had low frequencies of all antibodies. Conclusion: SLE-associated pulmonary hypertension disproportionately affects African–American patients. Pulmonary hypertension in SLE is defined by five autoantibody clusters. Antiphospholipid antibodies, anti-Ro and anti-La positivity, serological activity, and age at pulmonary hypertension diagnosis significantly differed across clusters, possibly indicating different pathophysiological mechanisms.